2017
DOI: 10.1155/2017/2421459
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Validation of Hub Genes Associated with Colorectal Cancer by Integrating PPI Network and Gene Expression Data

Abstract: Although hundreds of colorectal cancer- (CRC-) related genes have been screened, the significant hub genes still need to be further identified. The aim of this study was to identify the hub genes based on protein-protein interaction network and uncover their clinical value. Firstly, 645 CRC patients' data from the Tumor Cancer Genome Atlas were downloaded and analyzed to screen the differential expression genes (DEGs). And then, the Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Then, downloaded samples and corresponding clinical data were cross-referenced by TCGA barcodes. Some patients do not meet the following criteria were eliminated: [ 1 ] a histological diagnosis of CRC [ 2 ] patients with complete clinical features including sex, age, tumor location, local invasion, lymph node metastasis, distal metastasis, differentiation grade, pathologic stage, survival information; [ 3 ] patients were still alive at least 1 month after initial pathologic diagnosis; [ 4 ] patients with corresponding RNA-Seq data. To generate the AS profiles for each CRC patient, SpliceSeq, a java application that unambiguously quantify the inclusion level of each exon and splice junction, was used to evaluate the RNA splicing patterns as previous described [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, downloaded samples and corresponding clinical data were cross-referenced by TCGA barcodes. Some patients do not meet the following criteria were eliminated: [ 1 ] a histological diagnosis of CRC [ 2 ] patients with complete clinical features including sex, age, tumor location, local invasion, lymph node metastasis, distal metastasis, differentiation grade, pathologic stage, survival information; [ 3 ] patients were still alive at least 1 month after initial pathologic diagnosis; [ 4 ] patients with corresponding RNA-Seq data. To generate the AS profiles for each CRC patient, SpliceSeq, a java application that unambiguously quantify the inclusion level of each exon and splice junction, was used to evaluate the RNA splicing patterns as previous described [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite advances in screening, diagnosis, and curative resection, colorectal cancer (CRC) is still one of the leading causes of cancer-related death worldwide [ 1 ]. In addition, it's clinical outcome for individual cases remains unsatisfactory because optimal management and individual therapy strategies still present great challenges [ 2 ]. At present, surgical resection is the only potentially curative therapy for CRC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-X-C motif chemokine ligand 3 (CXCL3) is a member of the CXC chemokine family, and its expression is associated with various cancers, such as liver cancer [19], gastric cancer [20], breast cancer [21], prostate cancer [22], and non-small cell cancer [23]. Meanwhile, some scholars have explored CXCL3 in the CRC, and their ndings consistently reveal that the expression of CXCL3 in cancer tissues is signi cantly higher than that in normal tissues [24,25]. The research indicated that there was no signi cant difference in CXCL3 expression between non-metastatic and low metastatic colon cancer cells compared with highly metastatic colon cancer cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing (RNA-Seq) and microarrays, the most representative methods of this technology, are mature enough for use in commercial applications ( Mantione et al, 2014 ; Zhang et al, 2015 ). During the past decades, the genome-wide transcriptional analysis of gene expression has become critically important to gain better insight into the biological processes of HCC and other types of cancer ( Jin et al, 2015 ; Xiong et al, 2017 ). In addition to the aberrant expression of transcripts, studies have focused on different molecular levels (multi-level omics), including copy number variation, epigenetic modifications, nucleotide polymorphisms, and DNA methylation, especially in HCC ( Lee et al, 2016 ; Lin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%